1995
DOI: 10.1073/pnas.92.16.7262
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis syntaxin homologue isolated by functional complementation of a yeast pep12 mutant.

Abstract: The syntaxin family of integral membrane proteins are thought to function as receptors for transport vesicles, with different isoforms of this family localized to various membranes throughout the cell. The yeast Pepl2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 44 publications
(36 reference statements)
2
49
0
1
Order By: Relevance
“…One example is that of the yeast PEP12 gene mentioned above. At least three genes in Arabidopsis are closely related in sequence to yeast PEP12: AtPEP12 (Bassham et al, 1995), AtVAM3 (Sato et al, 1997), and AtPLP (Zheng et al, 1999a). It is not clear whether this represents a specialization of function or simply redundancy between these three genes.…”
Section: Are Plant Cells Just Yeast Cells With Chloroplasts?mentioning
confidence: 99%
See 1 more Smart Citation
“…One example is that of the yeast PEP12 gene mentioned above. At least three genes in Arabidopsis are closely related in sequence to yeast PEP12: AtPEP12 (Bassham et al, 1995), AtVAM3 (Sato et al, 1997), and AtPLP (Zheng et al, 1999a). It is not clear whether this represents a specialization of function or simply redundancy between these three genes.…”
Section: Are Plant Cells Just Yeast Cells With Chloroplasts?mentioning
confidence: 99%
“…In some cases, the available evidence still suggests that the yeast and Arabidopsis proteins have equivalent functions: e.g. the ER-to-Golgi trafficking proteins Sar1p and Sec12p (d'Enfert et al, 1992) and the prevacuolar t-SNARE (SNAP receptor; a protein found on the target membrane required for vesicle fusion with that membrane) Pep12p (Bassham et al, 1995). However, several examples have come to light recently in which the correlation between localization and/or function of protein trafficking machinery in yeast and plants is not so clear.…”
Section: Are Plant Cells Just Yeast Cells With Chloroplasts?mentioning
confidence: 99%
“…A second polyclonal antiserum raised to amino acids 1 to 129 of AtPEP12p fused to a C-terminal hexa-His tag (AtPEP12[1-129]-H 6 ) was generated as follows: PCR was performed on the cloned cDNA of AtPEP12 (Bassham et al, 1995) to generate EcoRI and NdeI sites at the 5Ј-end of the open reading frame (ORF) (primer F: 5Ј-G GAA TTC CAT ATG AGT TTC CAA AGA TCT-3Ј, EcoRI site underlined, NdeI site in bold; primer R: 5Ј-GGG TCT TTG TAT GTT TCC ATA GAT TCG C-3Ј). This product was digested with EcoRI and HindIII (found internal to primer R at the 3Ј-end of the AtPEP12 ORF), and cloned into similarly digested pBluescript KS (Stratagene, La Jolla, CA) to create pNde-AtPEP12; the sequence of this construct was verified by the Michigan State University Sequencing Facility.…”
Section: Antibody Production and Purificationmentioning
confidence: 99%
“…The process by which these vesicles differentiate the correct target membrane from all other organelles is believed to be mediated by integral membrane proteins called SNAREs (soluble N-ethylmaleimide sensitive factor attachment protein receptors) that reside on the surface of the vesicle (vSNAREs) and target membrane (t-SNAREs; for review, see Sanderfoot and Raikhel, 1999). This process has been best studied in yeast (Saccharomyces cerevisiae) and mammalian cells, although SNAREs are now known in Arabidopsis as well (Bassham et al, 1995;Lukowitz et al, 1996;Sato et al, 1997;Leyman et al, 1999;Zheng et al, 1999aZheng et al, , 1999b.…”
mentioning
confidence: 99%
“…Several of these mutants have now been used in complementation screens with plant cDNA libraries. The Arabidopsis counterparts to the yeast t-SNAREs Pep12p and Vam3p (Bassham et al, 1995 ;BarPeled & Raikhel, 1997 ;Sato et al, 1997), and at least one group of Arabidopsis and Nicotiana GTPase proteins (Bednarek et al, 1994 ;Takeuchi et al, 1998) were first characterized in this manner.…”
Section: Identifying Secretory Proteins In Plantsmentioning
confidence: 99%